DIGITAL MARKETING FOR ACCOMMODATION SERVICE BUSINESSES IN BAWEAN ISLAND, GRESIK - Dian Yulie Reindrawati; Jiwangga H Nata; Umi F Bascha; Nur E Suriani (Darmabakti Cendekia: Journal of Community Service and Engagements, 2022)
Background: The success of developing a tourist village starts from the accommodation manager at a tourist site and depends on the level of acceptance and support of the local community. Local communities will later act as hosts and become important actors in the development of tourist villages in all stages, starting from planning, monitoring, and implementation so that their success will also be enjoyed with a multiplier effect on the surrounding community. However, tourists often do not get information because of the lack of promotion in the media about the condition of the tourist area and also the readiness of accommodation. Objective: To provide digital marketing training for accommodation service businesses on Bawean Island. Methods: The method used is training and mentoring related to what digital marketing is, the urgency of using digital marketing, how to compose interesting content, execution of social media usage and also making attractive social media layouts. Results: The result of this activity is the implementation of digital marketing in the partner accommodation business. This activity was also accompanied by the creation of a film concept about the activities of the community community in Bawean Island which was accurate. Conclusion: the community, in this case the business actors, is still traditional. They still really need information and knowledge about digital marketing promotion efforts. Therefore, this tourism training activity is important so that the knowledge and skills of the tourism business community will increase.